Step-by-step removal method for impurities Pb and S in copper-rich alloy obtained through selective reduction of copper slag
By using SiO2 and Cu2O in step-by-step reaction with Pb and S in the copper-rich alloy, efficient removal of impurities Pb and S in the copper-rich alloy obtained by selective reduction of copper slag is achieved, solving the problems of high cost and large carbon emissions in the prior art, and improving the alloy performance.
Patent Information
- Application Number
- CN202510078898.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-01-17
- Publication Date
- 2025-04-11
AI Technical Summary
The prior art is difficult to efficiently remove impurities Pb and S in copper-rich alloys obtained from selective reduction of copper slag, and desulfurizers and reducing agents are often required, resulting in increased costs and carbon emissions.
The step-by-step removal method is adopted. First, the Pb in the reaction of SiO2 and PbO in the copper-rich prefabricated alloy under an inert atmosphere was used to remove Pb, and then the reaction of Cu2O and Cu2S was used to remove S, so as to achieve step-by-step removal of impurities Pb and S.
It effectively reduces the Pb and S content in the copper-rich alloy, avoids the need to add reducing agents, reduces carbon emissions, and improves the conductivity and high-temperature plasticity of the alloy.
Smart Images

Figure BDA0005247905040000051 
Figure BDA0005247905040000052 
Figure BDA0005247905040000062
Abstract
Description
Technical Field
[0001] The present application relates to the technical field of pyrometallurgy, and in particular to a method for removing impurities Pb and S in a copper-rich alloy obtained by selective reduction of copper slag in steps. Background Art
[0002] Copper-rich alloys are widely used in electronics, mechanical engineering, chemical engineering and many other fields due to their excellent electrical conductivity, thermal conductivity, ductility and corrosion resistance. At present, the main preparation method of copper-rich alloys is alloying, that is, adding a certain amount of alloying elements to the copper matrix to form a solid solution or a supersaturated solid solution, so that the copper matrix undergoes lattice distortion or precipitation strengthening phases by aging, thereby obtaining high-strength and high-conductivity copper-rich alloys. With the continuous development of comprehensive solid waste recycling technology, the preparation of copper-rich alloys by selective reduction of copper slag to achieve the simultaneous efficient and high-value recovery of valuable metals such as copper and iron from slag has gradually emerged. Related studies have used coal powder, natural gas and other reducing agents to reduce and deplete to prepare crude copper-iron alloys, but a large amount of impurities S and Pb in copper slag are added to the alloy during the depletion process, which seriously affects the physical and chemical properties of the alloy. The sulfur element is dispersed in the alloy as Cu2S, which reduces the electrical conductivity and thermal conductivity of the alloy and directly affects the machinability of the alloy. The presence of impurity Pb will reduce the high-temperature plasticity of the alloy and directly affect its application. Therefore, removing impurity S and Pb elements from copper-iron alloys is of great significance in improving alloy properties and promoting their popularization and application.
[0003] The patent application number is 201611056424.5, a method for achieving deep depletion of copper slag by step-by-step injection of multiple gases. The application uses the waste heat of molten copper slag to first convert copper matte into oxides through a gasification desulfurization process, and then selectively reduces the oxides through a reducing agent to obtain a copper-iron alloy phase. The patent removes sulfur by allowing sulfur to enter the flue gas in the form of sulfur dioxide through oxidation. However, the oxidation process inevitably leads to further oxidation of a large amount of Fe, thereby increasing the amount of reducing agent used in the back end and increasing costs.
[0004] The patent application number is 202310211184.5, a desulfurization method and copper-iron alloy of a high-sulfur copper-iron alloy produced from copper smelting slag. The high-sulfur copper-iron alloy is heated to the desulfurization temperature together with the desulfurizer and the reducing agent for deep desulfurization. After the desulfurization is completed, the low-sulfur copper-iron alloy is separated from the sulfur-containing slag after static sedimentation. This patent can achieve deep desulfurization of high-sulfur copper-iron alloy by adding a desulfurizer and a reducing agent to the molten high-sulfur copper-iron alloy. Although this method achieves the removal of sulfur in the alloy, it requires the use of a desulfurizer and a reducing agent at the same time. The consumption of the reducing agent in the desulfurization process will produce carbon emissions.
[0005] Therefore, there is an urgent need to provide a method for efficiently removing impurity elements in copper slag without introducing new impurities, and with high efficiency and low carbon emissions. Summary of the invention
[0006] In order to solve or partially solve the problems existing in the related art, the present application provides a step-by-step removal method of impurities Pb and S in copper-rich alloys obtained by selective reduction of copper slag, which can effectively remove impurities Pb and S in copper-rich alloys obtained by reduction of copper slag.
[0007] The present application provides a step-by-step method for removing impurities Pb and S in a copper-rich alloy obtained by selective reduction of copper slag, comprising the following steps:
[0008] S1, using pulverized coal to selectively reduce and deplete copper slag in a high temperature inert atmosphere to obtain a copper-rich prefabricated alloy;
[0009] S2, adding SiO2 to the copper-rich prefabricated alloy, heating to a preset temperature under an inert atmosphere and keeping the temperature, removing the impurity Pb element to obtain an intermediate product alloy;
[0010] S3, adding Cu2O to the intermediate product alloy to remove the S element, and obtaining a copper-rich alloy with low impurity Pb and S content by sedimentation separation.
[0011] Optionally, in step S2, the SiO2 addition ratio is 0.2%-1.5% of the total mass of the copper-rich prefabricated alloy.
[0012] Optionally, in step S3, the Cu2O addition ratio is 3%-5% of the total mass of the intermediate product alloy.
[0013] Optionally, in step S2, the preset temperature is 1425° C. and the insulation time is 60-90 minutes.
[0014] Optionally, the temperature for removing the S element in step S3 is 1425° C., and the insulation time is 90-120 min.
[0015] Optionally, in step S1, the selective reduction and depletion temperature of copper slag is 1425° C., and the reaction time is 120 min.
[0016] Optionally, the copper slag in step S1 includes smelting slag or blowing slag.
[0017] Based on the occurrence characteristics of impurity elements Pb and S in the copper-rich prefabricated alloy, the present application proposes to use the property of impurity Pb as an alkaline impurity to use acidic flux SiO2 to react with PbO generated by oxidation of Pb in the alloy to form slag, so as to remove the impurity Pb (reaction 1). Furthermore, since a large amount of S in the copper-rich prefabricated alloy exists in the form of Cu2S, the chemical reaction between Cu2O and Cu2S is used to react S in the copper-rich prefabricated alloy to SO2 for removal, and the reaction principle is shown in reaction 2. Using Cu2O as a desulfurizing agent, the impurity S is removed without introducing new impurities.
[0018] PbO+SiO2=PbSiO3 (1)
[0019] 2Cu2O+Cu2S=6Cu+SO2 (2)
[0020] The technical solution provided by this application may have the following beneficial effects:
[0021] 1) The present application removes the impurities Pb and S in the copper-rich alloy in two steps, thereby avoiding the adverse effects of the simultaneous use of two additives on the impurity removal.
[0022] 2) In the first stage of the present application, SiO2 is added to form a slag reaction to remove Pb. SiO2 has a good Pb removal effect and finally exists in the form of slag phase, which is easy to separate from the alloy. The second stage uses Cu2O reaction for desulfurization. Cu2O will not introduce new impurities while achieving S removal, and can improve the Cu grade in the final alloy, adjust the copper content in the copper-rich alloy, and achieve the step-by-step removal of impurities Pb and S in the copper-rich alloy.
[0023] 3) The present invention can remove Pb and S from copper-rich alloys obtained by selective reduction of different types of copper slags, and has a wide range of applicability to sulfur content in the alloys.
[0024] 4) The step-by-step removal process of impurities Pb and S does not require the addition of reducing agents, has no additional carbon emissions, and is environmentally friendly.
[0025] It should be understood that the foregoing general description and the following detailed description are exemplary and explanatory only and are not restrictive of the present application. BRIEF DESCRIPTION OF THE DRAWINGS
[0026] The above and other objects, features and advantages of the present application will become more apparent through a more detailed description of exemplary embodiments of the present application in conjunction with the accompanying drawings, wherein the same reference numerals generally represent the same components in the exemplary embodiments of the present application.
[0027] Figure 1 It is a process flow chart of the step-by-step removal method of impurities Pb and S in the copper-rich alloy obtained by selective reduction of copper slag shown in the present application. DETAILED DESCRIPTION
[0028] The embodiments of the present application will be described in more detail below with reference to the accompanying drawings. Although the embodiments of the present application are shown in the accompanying drawings, it should be understood that the present application can be implemented in various forms and should not be limited by the embodiments described herein. On the contrary, these embodiments are provided to make the present application more thorough and complete, and to fully convey the scope of the present application to those skilled in the art.
[0029] The present application provides a step-by-step method for removing impurities Pb and S in a copper-rich alloy obtained by selective reduction of copper slag, comprising the following steps:
[0030] S1, using pulverized coal to selectively reduce and deplete copper slag in a high temperature inert atmosphere to obtain a copper-rich prefabricated alloy;
[0031] The copper slag includes smelting slag or blowing slag. The selective reduction and depletion temperature of the copper slag is 1425°C and the reaction time is 120 minutes.
[0032] S2, adding SiO2 to the copper-rich prefabricated alloy, heating to a preset temperature under an inert atmosphere and keeping the temperature, removing the impurity Pb element to obtain an intermediate product alloy;
[0033] The SiO2 addition ratio is 0.2%-1.5% of the total mass of the copper-rich prefabricated alloy. The preset temperature is 1425℃. The holding time is 60-90min.
[0034] S3, adding Cu2O to the intermediate product alloy to remove the S element, and obtaining a copper-rich alloy with low impurity S and Pb content by sedimentation separation.
[0035] The addition ratio of Cu2O is 3%-5% of the total mass of the intermediate product alloy. The temperature for removing S element is 1425℃, and the holding time is 90-120min.
[0036] Example 1
[0037] like Figure 1 As shown, the step-by-step removal method of impurities Pb and S in the copper-rich alloy obtained by selective reduction of copper slag comprises the following steps:
[0038] 8.2% anthracite was added to 500g of converter blowing slag (its composition is shown in Table 1, Cu and Fe contents are 3.8% and 44% respectively, and the main phases are Fe3O4 and Fe2SiO4) and reduced for 120min at 1425℃ in nitrogen atmosphere to obtain a copper-rich prefabricated alloy (composition is shown in Table 2). The copper-rich prefabricated alloy obtained by selective reduction of copper slag has Cu and Fe contents of 16.81% and 78.93% respectively, and impurity elements S and Pb contents of 1.81% and 0.52% respectively. 1% SiO2 was added to the copper-rich prefabricated alloy, and the temperature was raised to 1425℃ in an inert atmosphere and kept for 90min to remove the impurity Pb to prepare an intermediate product alloy, and its chemical composition is shown in Table 3. After the SiO2 flux was used to remove Pb, the Cu and Fe contents of the intermediate product alloy were 15.28% and 80.52% respectively, the impurity S content was 1.24%, and the impurity Pb content was less than 0.01%. After removing the impurity Pb, 3% Cu2O was added to the intermediate product alloy at 1425°C and kept warm for 120 minutes. The sulfur was converted into SO2 through chemical reaction to remove the impurity S, and finally a copper-rich alloy was obtained (the composition is shown in Table 4). The Cu and Fe contents of the low-Pb, S-rich copper alloy were 17.25% and 78.43%, respectively, the S content was reduced to 0.59%, and the Pb content was less than 0.01%. By adding SiO2 to remove the impurity Pb in the first stage and removing the impurity S in the second stage of Cu2O, the Pb content in the copper-rich prefabricated alloy was finally reduced to less than 0.01% and the S element was reduced to 0.59%.
[0039] Table 1 Element composition of blowing slag / %
[0040]
[0041] Table 2 Chemical composition of copper-rich pre-alloy obtained by selective reduction of copper slag / %
[0042]
[0043] Table 3 Chemical composition of intermediate product alloy of Example 1 / %
[0044]
[0045]
[0046] Table 4 Chemical composition of copper-rich alloy in Example 1 / %
[0047]
[0048] The copper-rich alloy with low contents of impurities S and Pb obtained in this embodiment has the content of impurity Pb reduced to below 0.01% and the S element reduced to 0.59% after de-Pbing by SiO2.
[0049] Example 2
[0050] like Figure 1 As shown, the step-by-step removal method of impurities Pb and S in the copper-rich alloy obtained by selective reduction of copper slag comprises the following steps:
[0051] 8.2% anthracite was added to 500g of converter blowing slag (whose composition is the same as that in Table 1 of Example 1) and reduced for 120min at 1425℃ in nitrogen atmosphere to obtain a copper-rich prefabricated alloy (the composition is as shown in Table 2 of Example 1). 0.2% SiO2 was added to the copper-rich prefabricated alloy and the temperature was raised to 1425℃ in an inert atmosphere and kept for 90min to remove the impurity Pb to prepare an intermediate product alloy, the chemical composition of which is shown in Table 5. After the SiO2 flux was used to remove the Pb, the Cu and Fe contents of the intermediate product alloy were 14.98% and 79.37%, respectively, the impurity S content was 1.35%, and the impurity Pb content was 0.29%. After the impurity Pb was removed, 3% Cu2O was added to the intermediate product alloy at 1425℃ and kept for 120min. The sulfur was converted into SO2 by chemical reaction to achieve the removal of the impurity S, and finally a copper-rich alloy (the composition is shown in Table 6) was obtained. The final low-Pb, S-rich copper alloy has Cu and Fe contents of 16.37% and 78.59% respectively, S content is reduced to 0.63%, and Pb content is 0.11%. By adding SiO2 in the first stage to remove the impurity Pb and combining it with Cu2O in the second stage to remove the impurity S, the Pb content in the copper-rich prefabricated alloy is finally reduced to 0.11% and the S element is reduced to 0.63%.
[0052] Table 5 Chemical composition of intermediate product alloy of Example 2 / %
[0053]
[0054] Table 6 Chemical composition of copper-rich alloy in Example 2 / %
[0055]
[0056] The copper-rich alloy with low contents of impurities S and Pb obtained in this embodiment has the content of impurity Pb reduced to 0.11% and the S element reduced to 0.63% after de-Pbing by SiO2.
[0057] Example 3
[0058] like Figure 1 As shown, the step-by-step removal method of impurities Pb and S in the copper-rich alloy obtained by selective reduction of copper slag comprises the following steps:
[0059] 8.2% anthracite was added to 500g of converter blowing slag (whose composition is the same as that in Table 1 of Example 1) and reduced for 120min at 1425℃ in nitrogen atmosphere to obtain a copper-rich prefabricated alloy (the composition is as shown in Table 2 of Example 1). 1.5% SiO2 was added to the copper-rich prefabricated alloy and the temperature was raised to 1425℃ in an inert atmosphere and kept for 90min to remove the impurity Pb to prepare an intermediate product alloy, the chemical composition of which is shown in Table 7. After the SiO2 flux was used to remove the Pb, the Cu and Fe contents of the intermediate product alloy were 15.31% and 80.71% respectively, the impurity S content was 1.17%, and the impurity Pb content was <0.01%. After the impurity Pb was removed, 3% Cu2O was added to the intermediate product alloy at 1425℃ and kept for 120min. The sulfur was converted into SO2 by chemical reaction to achieve the removal of the impurity S, and finally a copper-rich alloy (the composition is shown in Table 8) was obtained. The final low-Pb, S-rich copper alloy contains 17.36% Cu and 78.15% Fe, respectively, the S content is reduced to 0.54%, and the Pb content is less than 0.01%. By adding SiO2 to remove the impurity Pb in the first stage and combining it with Cu2O to remove the impurity S in the second stage, the Pb content in the copper-rich prefabricated alloy is finally reduced to less than 0.01% and the S element is reduced to 0.54%.
[0060] Table 7 Chemical composition of intermediate product alloy in Example 3 / %
[0061]
[0062] Table 8 Chemical composition of copper-rich alloy in Example 3 / %
[0063]
[0064] The copper-rich alloy with low contents of impurities S and Pb obtained in this embodiment has the content of impurity Pb reduced to below 0.01% and the S element reduced to 0.54% after SiO2 removal of Pb.
[0065] Example 4
[0066] like Figure 1 As shown, the step-by-step removal method of impurities Pb and S in the copper-rich alloy obtained by selective reduction of copper slag comprises the following steps:
[0067] 8.2% anthracite was added to 500g of converter blowing slag (whose composition is the same as that in Table 1 of Example 1) and reduced for 120min at 1425℃ in nitrogen atmosphere to obtain a copper-rich prefabricated alloy (the composition is as shown in Table 2 of Example 1). 1.5% SiO2 was added to the copper-rich prefabricated alloy and the temperature was raised to 1425℃ in an inert atmosphere and kept for 60min to remove the impurity Pb to prepare an intermediate product alloy, the chemical composition of which is shown in Table 9. After the SiO2 flux was used to remove the Pb, the Cu and Fe contents of the intermediate product alloy were 14.94% and 78.65% respectively, the impurity S content was 1.39%, and the impurity Pb content was 0.11%. After the impurity Pb was removed, 3% Cu2O was added to the intermediate product alloy at 1425℃ and kept for 120min. The sulfur was converted into SO2 by chemical reaction to achieve the removal of the impurity S, and finally a copper-rich alloy (the composition is shown in Table 10) was obtained. The final low-Pb, S-rich copper alloy contains 16.81% Cu and 77.98% Fe, 0.62% S and 0.05% Pb, respectively. By adding SiO2 to remove the impurity Pb in the first stage and Cu2O to remove the impurity S in the second stage, the Pb content in the copper-rich prefabricated alloy is reduced to 0.05% and the S element is reduced to 0.62%.
[0068] Table 9 Chemical composition of intermediate product alloy of Example 4 / %
[0069]
[0070] Table 10 Chemical composition of copper-rich alloy in Example 4 / %
[0071]
[0072] The copper-rich alloy with low contents of impurities S and Pb obtained in this embodiment has the content of impurity Pb reduced to 0.05% and the S element reduced to 0.62% after de-Pbing by SiO2.
[0073] Example 5
[0074] like Figure 1 As shown, the step-by-step removal method of impurities Pb and S in the copper-rich alloy obtained by selective reduction of copper slag comprises the following steps:
[0075] 8.2% anthracite was added to 500g of converter blowing slag (whose composition is the same as that in Table 1 of Example 1) and reduced for 120min at 1425℃ in nitrogen atmosphere to obtain a copper-rich prefabricated alloy (the composition is as shown in Table 2 of Example 1). 1% SiO2 was added to the copper-rich prefabricated alloy and the temperature was raised to 1425℃ in an inert atmosphere and kept warm for 90min to remove the impurity Pb to prepare an intermediate product alloy, the chemical composition of which is shown in Table 11. After the SiO2 flux was used to remove the Pb, the Cu and Fe contents of the intermediate product alloy were 15.19% and 80.37% respectively, the impurity S content was 1.27%, and the impurity Pb content was less than 0.01%. After the impurity Pb was removed, 5% Cu2O was added to the intermediate product alloy at 1425℃ and kept warm for 120min. The sulfur was converted into SO2 by chemical reaction to achieve the removal of the impurity S, and finally a copper-rich alloy (the composition is shown in Table 12) was obtained. The final low-Pb, S-rich copper alloy contains 17.41% Cu and 79.12% Fe, the S content is reduced to 0.51%, and the Pb content is less than 0.01%. By adding SiO2 to remove the impurity Pb in the first stage and Cu2O to remove the impurity S in the second stage, the Pb content in the copper-rich prefabricated alloy is reduced to less than 0.01% and the S element is reduced to 0.51%.
[0076] Table 11 Chemical composition of intermediate product alloy of Example 5 / %
[0077]
[0078] Table 12 Chemical composition of copper-rich alloy in Example 5 / %
[0079]
[0080] The copper-rich alloy with low content of impurities S and Pb obtained in this embodiment has a Pb content of less than 0.01% after SiO2 removal of Pb, and the S element is reduced to 0.51%.
[0081] Comparative Example 1
[0082] Compared with Example 1, Comparative Example 1 does not add SiO2 in the impurity element Pb removal stage. The specific steps are:
[0083] 8.2% anthracite was added to 500g of converter blowing slag (whose composition is the same as that in Table 1 in Example 1) and reduced for 120min at 1425°C in a nitrogen atmosphere to obtain a copper-rich prefabricated alloy (the composition is as shown in Table 2 in Example 1). The copper-rich prefabricated alloy was directly heated to 1425°C in an inert atmosphere and kept warm for 90min to remove the impurity Pb to prepare an intermediate product alloy, and its chemical composition is shown in Table 13. After direct heating treatment, the Cu and Fe contents of the intermediate product alloy were 14.34% and 78.81% respectively, the impurity S content was 1.47%, and the impurity Pb content was 0.36%. After removing the impurity Pb, 3% Cu2O was added to the intermediate product alloy, and kept warm for 120min. The sulfur was converted into SO2 by chemical reaction to achieve the removal of the impurity S, and finally a copper-rich alloy (the composition is shown in Table 14) was obtained. The final low-Pb, S-rich copper alloy has Cu and Fe contents of 15.38% and 79.21% respectively, the S content is reduced to 0.71%, and the Pb content is 0.31%.
[0084] Table 13 Chemical composition of intermediate product alloy of comparative example 1 / %
[0085]
[0086] Table 14 Chemical composition of copper-rich alloy in comparative example 1 / %
[0087]
[0088] The S content in the finally obtained copper-rich alloy is 0.71%, and the impurity element Pb content is 0.31%, which are higher than the copper-rich alloy with low impurity S and Pb contents obtained in Example 1 (Pb < 0.01%).
[0089] Comparative Example 2
[0090] Compared with Example 2, in Comparative Example 2, the amount of Cu2O added is reduced from 3% to 0.2% during the impurity element S removal stage. The specific steps are:
[0091] 8.2% anthracite was added to 500g of converter blowing slag (whose composition is the same as that in Table 1 of Example 1) and reduced for 120min at 1425°C in a nitrogen atmosphere to obtain a copper-rich prefabricated alloy (the composition is as shown in Table 2 of Example 1). 0.2% SiO2 was added to the copper-rich prefabricated alloy and the alloy was heated to 1425°C in an inert atmosphere and kept warm for 90min to remove the impurity Pb to prepare an intermediate product alloy, the chemical composition of which is shown in Table 15. The Cu and Fe contents of the intermediate product alloy were 14.53% and 78.94% respectively, the impurity S content was 1.39%, and the impurity Pb content was 0.26%. After removing the impurity Pb, 0.5% Cu2O was added to the intermediate product alloy and kept warm for 120min to convert sulfur into SO2 through chemical reaction to achieve the removal of impurity S, and finally a copper-rich alloy 8 (the composition is shown in Table 16) was obtained. The final low-Pb, S-rich copper alloy has Cu and Fe contents of 16.12% and 78.33% respectively, S content of 1.08% and Pb content of 0.15%.
[0092] Table 15 Chemical composition of intermediate product alloy of comparative example 2 / %
[0093]
[0094] Table 16 Chemical composition of copper-rich alloy in comparative example 2 / %
[0095]
[0096] The S content in the final copper-rich alloy is 1.08%, which is higher than the S content (0.63%) in the copper-rich alloy with low impurity S and Pb contents obtained in Example 2.
[0097] Comparative Example 3
[0098] Compared with Example 3, in Comparative Example 3, the holding time in the impurity element Pb removal stage is reduced from 90 min to 30 min. The specific steps are:
[0099] 8.2% anthracite was added to 500g of converter blowing slag (whose composition is the same as that in Table 1 of Example 1) and reduced for 120min at 1425℃ in nitrogen atmosphere to obtain a copper-rich prefabricated alloy (the composition is as shown in Table 2 of Example 1). 1.5% SiO2 was added to the copper-rich prefabricated alloy and the temperature was raised to 1425℃ in an inert atmosphere and kept warm for 30min to remove the impurity Pb to prepare an intermediate product alloy, the chemical composition of which is shown in Table 17. After the SiO2 flux was used to remove the Pb, the Cu and Fe contents of the intermediate product alloy were 14.81% and 78.16%, respectively, the impurity S content was 1.46%, and the impurity Pb content was 0.23%. After the impurity Pb was removed, 3% Cu2O was added to the intermediate product alloy at 1425℃ and kept warm for 120min. The sulfur was converted into SO2 by chemical reaction to achieve the removal of the impurity S, and finally a copper-rich alloy (the composition is shown in Table 18) was obtained. The final low-Pb, S-rich copper alloy contains 15.79% Cu and 77.06% Fe, respectively, the S content is reduced to 0.76%, and the Pb content is 0.14%. By adding SiO2 to remove the impurity Pb in the first stage and Cu2O to remove the impurity S in the second stage, the Pb content in the copper-rich prefabricated alloy is finally reduced to 0.14% and the S element is reduced to 0.76%.
[0100] Table 17 Chemical composition of intermediate product alloy of comparative example 3 / %
[0101]
[0102] Table 18 Chemical composition of copper-rich alloy in comparative example 3 / %
[0103]
[0104] The S content in the finally obtained copper-rich alloy is 0.76%, and the impurity element Pb content is 0.14%, which are higher than the copper-rich alloy with low impurity S and Pb contents obtained in Example 3 (Pb < 0.01%).
[0105] Comparative Example 4
[0106] Compared with Example 4, in Comparative Example 4, the holding time in the impurity element S removal stage is reduced from 90 min to 30 min. The specific steps are:
[0107] 8.2% anthracite was added to 500g of converter blowing slag (whose composition is the same as that in Table 1 of Example 1) and reduced for 120min at 1425℃ in nitrogen atmosphere to obtain a copper-rich prefabricated alloy (the composition is as shown in Table 2 of Example 1). 1.5% SiO2 was added to the copper-rich prefabricated alloy and the temperature was raised to 1425℃ in an inert atmosphere and kept for 60min to remove the impurity Pb to prepare an intermediate product alloy, the chemical composition of which is shown in Table 19. After the SiO2 flux was used to remove the Pb, the Cu and Fe contents of the intermediate product alloy were 15.19% and 77.38%, respectively, the impurity S content was 1.33%, and the impurity Pb content was 0.13%. After the impurity Pb was removed, 3% Cu2O was added to the intermediate product alloy at 1425℃ and kept for 60min. The impurity S was removed by chemical reaction by converting sulfur into SO2, and finally a copper-rich alloy (the composition is shown in Table 20) was obtained. The final low-Pb, S-rich copper alloy contains 16.35% Cu and 77.27% Fe, the S content is reduced to 0.81%, and the Pb content is 0.06%. By adding SiO2 to remove the impurity Pb in the first stage and Cu2O to remove the impurity S in the second stage, the Pb content in the copper-rich prefabricated alloy is finally reduced to 0.06% and the S element is reduced to 0.81%.
[0108] Table 19 Chemical composition of intermediate product alloy of comparative example 4 / %
[0109]
[0110] Table 20 Chemical composition of copper-rich alloy of comparative example 4 / %
[0111]
[0112] The content of impurity element Pb in the finally obtained copper-rich alloy is 0.06%, and the content of S is 0.81%, which are higher than the copper-rich alloy with low impurity S and Pb contents obtained in Example 4 (S content is 0.62%).
[0113] As can be seen from the above, in Example 1, SiO2 is added to the slag-forming reaction to remove Pb, and Cu2O is used to remove S. The content of impurity Pb in the obtained copper-rich alloy is less than 0.01%, and the content of impurity S is 0.59%. In Comparative Example 1, no SiO2 is added, and the content of impurity Pb in the obtained copper-rich alloy is 0.31%, which is higher than the S and Pb contents of the copper-rich alloy obtained in Example 1. It can be seen that the use of SiO2 in the present application has a good effect in removing Pb impurities.
[0114] In comparative example 2, the amount of Cu2O added was reduced from 3% to 0.2% during the removal of the impurity element S, and the S content in the obtained copper-rich alloy was 1.08%, which was higher than the S content (0.63%) in the alloy in Example 2. It can be seen that the application has a good effect on removing impurity S by using a Cu2O addition ratio of 3%-5% of the total mass of the intermediate product alloy.
[0115] In comparative example 3, the holding time in the impurity element Pb removal stage is reduced from 90 min to 30 min, and the S content in the finally obtained copper-rich alloy is 0.76%, and the impurity element Pb content is 0.14%, which are higher than the low S, Pb copper-rich alloy obtained in Example 3 (Pb < 0.01%). In comparative example 4, the holding time in the impurity element S removal stage is reduced from 90 min to 30 min. The impurity element Pb content in the obtained copper-rich alloy is 0.06%, and the S content is 0.81%, which are higher than the low S, Pb copper-rich alloy obtained in Example 4 (S content 0.62%). It can be seen that a copper-rich alloy with low Pb and S contents can be obtained by adopting a holding time of 60-90 min in the impurity element Pb removal stage of the present application and a holding time of 90-120 min in the impurity element S removal stage.
[0116] In summary, the present application adopts SiO2 slag forming reaction to remove Pb, adopts Cu2O reaction to remove S, optimizes the addition ratio of SiO2 and Cu2O, optimizes the holding time, and obtains a copper-rich alloy with low content of impurities Pb and S.
[0117] The embodiments of the present application have been described above, and the above description is exemplary, not exhaustive, and is not limited to the disclosed embodiments. Many modifications and changes will be apparent to those of ordinary skill in the art without departing from the scope and spirit of the described embodiments. The selection of terms used herein is intended to best explain the principles of the embodiments, practical applications, or improvements to the technology in the market, or to enable other persons of ordinary skill in the art to understand the embodiments disclosed herein.
Claims
1. A step-by-step method for removing impurities Pb and S from a copper-rich alloy obtained by selective reduction of copper slag, characterized in that: The following steps are involved: S1, using pulverized coal to selectively reduce and deplete copper slag in a high temperature inert atmosphere to obtain a copper-rich prefabricated alloy; S2, adding SiO2 to the copper-rich prefabricated alloy, heating to a preset temperature under an inert atmosphere and keeping the temperature, removing the impurity Pb element to obtain an intermediate product alloy; S3, adding Cu2O to the intermediate product alloy to remove the S element, and obtaining a copper-rich alloy with low contents of impurities Pb and S by sedimentation separation.
2. The step-by-step removal method according to claim 1, characterized in that: In step S2, the SiO2 addition ratio is 0.2%-1.5% of the total mass of the copper-rich prefabricated alloy.
3. The step-by-step removal method according to claim 1, characterized in that: In step S3, the Cu2O addition ratio is 3%-5% of the total mass of the intermediate product alloy.
4. The step-by-step removal method according to claim 1, characterized in that: The preset temperature in step S2 is 1425° C. and the holding time is 60-90 minutes.
5. The step-by-step removal method according to claim 1, characterized in that: The temperature for removing the S element in step S3 is 1425° C., and the insulation time is 90-120 min.
6. The step-by-step removal method according to claim 1, characterized in that: In the step S1, the temperature for selective reduction and depletion of copper slag is 1425° C., and the reaction time is 120 min.
7. The step-by-step removal method according to claim 1, characterized in that: The copper slag in step S1 includes smelting slag or blowing slag.
Citation Information
Patent Citations
A method for step-by-step multi-component gas injection to realize deep depletion of copper slag
CN106756062B
Method for realizing deep depletion on copper slag through multielement gas substep injection
CN106756062A
Copper slag dilution method
CN114150157A
Desulfurization method of high-sulfur copper-iron alloy produced from copper smelting slag and copper-iron alloy
CN116162846A
An Improved Process for Eliminating Lead and other Impurities, such as Arsenic and Antimony, from a Plumbiferous Copper Matte, Ore or Alloy and simultaneously Recovering the Copper as Metal.
GB190819585A